(untitled) (International Journal of Latest Technology in Engineering Management & Applied Science, 2026)
Quality education is very important for a nation’s prosperity and development. NEP 2020 has emphasized the holistic development of students. For quality education and holistic development innovative way of teaching as well as innovative evaluative systems are needed. Authentic assessment approach helps students to demonstrate their knowledge and skills in different ways. Authentic tasks may include making projects, creating artwork or videos or other products. In the present study, researchers try to find out the academic performance on the basis of an authentic assessment approach (doing project on infectious diseases) of secondary students of Uttar Dinajpur District of West Bengal in life science concerning location (rural and urban) and gender (female and male). Descriptive Survey Method was applied for this study. The data was collected from 202 students of 10th standard students of secondary schools in Uttar Dinajpur district of West Bengal in life science through a probability sampling technique. There are some socio-economic and school level variables that can influence performance, to control this researcher took some classes in rural and urban schools to guide them on authentic assessment approach. From the analysis and interpretations of the result it has been found that, the boys’ students had better academic performance than the girls’ students when an authentic assessment approach was applied. The urban students had better academic performance than the rural students in case of the authentic assessment approach. In this perspective, proper guidance, counseling and orientation programs for an authentic assessment approach should be organized for the teachers, and the students to know about the importance of an authentic assessment approach in the secondary school for holistic development, because when student apply their knowledge and skill at the practical situation then only the proper utilization of knowledge and skill can happen (Mueller, 2008). Thus, the government should take the initiative to apply the authentic assessment approach for better performance of the students in life science along with other academic subjects.